Narrative justice - McGregor, Rafe (Rowman & Littlefield International, 2020)
Narrative representation -- Narrative representation and non-narrative representation -- Values of narrative -- Aesthetic education -- Criminal inhumanity -- Narrative criminology -- Contemporary aesthetic education -- Reading, detranscendentalisation, and epistemological performance -- Literary imagination, ethics, and impossibility -- Narrative understanding -- Empirical evidence -- Narrative ethics -- Ethical value and narrativity -- Ethicism -- Closural moral order -- Narrative knowledge -- Knowledge and narrativity -- Epistemic criterion -- Narrativity criterion -- Narrative justice -- Ethical knowledge and narrativity -- Fascist fictions -- Poetic justice? -- Narrative justice -- Narrative value -- Hyperbolic ethics and deconstructive politics -- Literature, empathy, and experimentation -- Conclusion, coherence, and correspondence -- Correlation, causation, and the law -- Gregory currie and martha nussbaum -- Responsibility for inhumanity -- Wars -- Charges -- Defending de man -- Commending Campbell -- Silence and deceit -- Silence and remorselessness -- The psychology of inhumanity -- In the heart of the country -- The person of the torturer -- In the heart of the whore -- The problem that troubles the novelist -- Undermining inhumanity -- Narrative strategies -- White genocide -- Crusader -- Reducing violent extremism -- Coda : methodology?